2019
DOI: 10.1108/ijcma-06-2019-0097
|View full text |Cite
|
Sign up to set email alerts
|

Design teams management of conflict in reaching consensus

Abstract: Purpose The purpose of this paper is to explore the conversation activities of design teams to negotiate task conflict and reach consensus. Design/methodology/approach Four case studies were conducted to analyse the conversation activities that teams use in the course of design projects. Findings The conversation activities that teams used to negotiate conflict and bring about consensus were identified. These conversation activities are associated with collaboration, communication and social skills enablin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 72 publications
(147 reference statements)
2
5
0
Order By: Relevance
“…Team members also regularly built on the arguments of others in order to build on a position being advocated to the group. This concurs with the literature which shows that this is a differentiating factor between experts and novices during episodes of conflict in design problem solving [91].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Team members also regularly built on the arguments of others in order to build on a position being advocated to the group. This concurs with the literature which shows that this is a differentiating factor between experts and novices during episodes of conflict in design problem solving [91].…”
Section: Discussionsupporting
confidence: 92%
“…This required a balance in the management of the conflict in that, while task conflict led to a creative rethink on solution paths, it was important that task conflict did not stifle creative thinking in the flow of alternative ideas. This supports Kiernan et al [91] who showed that task conflict impacts positively only at certain stages of the creative process, the problem definition and concept development phases. While they recommend moderate levels of conflict at these phases they argue that conflict has the potential to have a damaging impact at the ideation phase by stifling the fluency of ideas.…”
Section: Discussionsupporting
confidence: 87%
“…A finding which requires further exploration is that close-mindedness and trust are reciprocally influenced. It is suggesting that certain topics may not be openly discussed or that some barriers exist to effectively deal with conflict (Kiernan et al, 2019 ). Perhaps the perception of lack of trust between family and non-family members is a plausible explanation which merits further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Task conflict enhances decision making due to the presentation of the different perspectives of team members (Wu 2020). Task conflict positively affects decision making, because it is considered to increase information and knowledge sharing (Kiernan et al 2019;Susskind and Odom-reed 2019).…”
Section: Factor Authorsmentioning
confidence: 99%